Purpose and Leading Characteristics of Jadid Travel Letters - Nematova Khulkar Abdulbakievna (Zien Journals, 2022)
With the efforts of the Jadids, who reformed many aspects of society with both practical and creative activities, travelogues of a specific conceptual purpose, works of a travelogue nature, emerged. This article explains the main purpose, content and peculiarities of Jadid travelogues.
Keywords: enlightened tourists; “crystallization”; comparison; national awakening literature